2019
DOI: 10.7752/jpes.2019.04374
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background:Physical activity allows sport athletes some systemic adjustments that lead to a better performance when compared to sedentary people. However, the real difference that the respiratory system may present between the two populations has yet to be established. This study aimed at evaluating the effects of physical activity on aerobic capacity, pulmonary function and respiratory muscle strength by determining thecorrelation among athletes and sedentary people. Methods:The study sample consisted of 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Long-term endurance and strength training, high-intensity inspiratory muscle training, and respiratory physiotherapy have also been reported to improve dyspnoea and optimize pulmonary and cardiorespiratory function in COPD patients (Greulich et al, 2014). Exercise has also been reported to improve aerobic ability and help optimize the respiratory (Campoi et al, 2019), metabolic parameters (Arovah & Heesch, 2021), and immune systems (Huntula et al, 2022;Mohamed & Alawna, 2020). The findings of this present study, thus, extend the literature by supporting the acute effect of concurrent exercise combined with breathing exercise in improving pulmonary function among women with post-COVID-19 syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term endurance and strength training, high-intensity inspiratory muscle training, and respiratory physiotherapy have also been reported to improve dyspnoea and optimize pulmonary and cardiorespiratory function in COPD patients (Greulich et al, 2014). Exercise has also been reported to improve aerobic ability and help optimize the respiratory (Campoi et al, 2019), metabolic parameters (Arovah & Heesch, 2021), and immune systems (Huntula et al, 2022;Mohamed & Alawna, 2020). The findings of this present study, thus, extend the literature by supporting the acute effect of concurrent exercise combined with breathing exercise in improving pulmonary function among women with post-COVID-19 syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate the potential role of RM training in weakening metabolic reflexes of inspiratory muscles, thereby improving oxygen and blood supply to limb muscles during high-intensity exercise, achieving the effect of delaying muscle fatigue and enhancing exercise performance [25]. Campoi et al demonstrated that PA associated with soccer can improve aerobic capacity, lung function, and inspiratory muscle strength, and there is a positive correlation between these variables [26]. This is another example of how RM capacity is a crucial part of football.…”
Section: Impact On Team Playersmentioning
confidence: 96%